Assessment of the vitamin d levels effect on the course of the first trimester of pregnancy - I. V. Kovalevа; M. O. Bakleicheva; O. N. Bespalova (Медицинский совет, 2022)
Introduction. The course of physiological pregnancy is provided by many complementary factors. Thus, a deficiency in one of the links of the metabolic network contributes to the development of an imbalance in the work of the whole organism, which ensures the growth and development of the embryo from the first days of gestation. It has been proven that vitamin D can act as an immune regulator during implantation, providing a protective effect in whole period of pregnancy.Aim. The aim of this study is assessed the features of the course of pregnancy in patients with different levels of vitamin D in the blood in the first trimester.Materials and methods. A prospective multicenter randomized study was conducted in the North-West region of the Russian Federation among 88 pregnant women in the first trimester of gestation (up to 13 weeks). All patients were divided into 3 groups depending on the initial level of vitamin D (group 1–14 women with a 25(OH)D < 10 ng/ml, group 2–62 pregnant women from 10 to 30ng/ml, group 3–12 pregnant women with a vitamin D content > 30 ng/ml).Results. In group 1.86% of patients with severe vitamin D deficiency were diagnosed with threatened miscarriage, which is significantly higher than in group 3 (85.7% and 33.3%, χ2 = 7.490, p = 0.007). At the same time, retrochorial hematoma in group 1 occurred 3.5 times more often than in group 3 (57.1% and 16.67%, respectively, χ2 = 4.473, p = 0.035). Subsequently, every 4th woman from the group with vitamin D deficiency gave birth earlier than expected, which was not observed among patients from group 3 (25%, 0%, χ2 = 1.231, p = 0.268).Conclusion. Prescribing cholecalciferol vitamin replacement therapy as part of complex preserving therapy for threatening miscarriage, followed by monitoring its blood level and deviating from normal parameters, contributing to a favorable course of pregnancy and improving perinatal outcomes.